Promoting sustainable entrepreneurship in training and education: The role of entrepreneurial culture - Zahrani, Aida Ahmed (Frontiers in Environmental Science, 2022)
The main purpose of this research was to investigate how universities may help Saudi Arabian students who are planning to become entrepreneurs promote sustainability development goals. The intersection of ecological development and entrepreneurship is referred to as "sustainable entrepreneurship." Entrepreneurs want to provide practical educational solutions. Thus, this study seeks to fill this gap by developing a new model for measuring the relationships between entrepreneurial culture, sustainability training, and sustainability education in Saudi Arabia. A quantitative research 'survey questionnaire' found in the human relations theory of sustainable entrepreneurship was used to collect data. This study looked at the impact of three dimensions connected to the role of entrepreneurship in higher education using AMOS and Structural Equation Modelling (SEM). The data (n = 252) was examined using AMOS and SEM. Therefore, this study specifies 37 items, three of which are the most important. 1) a sustainable entrepreneurial culture, 2) sustainability training, and 3) sustainability education. The findings imply that a sustained entrepreneurial culture has a good influence on training and education. Furthermore, sustainability training has a good influence on sustainability education. As a result, this research supports the extended human relations theory of the function of a sustainable entrepreneurial culture by indicating that the model anticipates university students increasing their entrepreneurial culture via training and education in higher education.